Adverse Events During Immunotherapy Against Grass Pollen‐Induced Allergic Rhinitis – Differences Between Subcutaneous and Sublingual Treatment. Issue 2 (3rd June 2015) - Aasbjerg, Kristian; Dalhoff, Kim Peder; Backer, Vibeke
Abstract: Allergic rhinitis (AR) triggered by grass pollen is a common disease, affecting millions of people worldwide. Treatment consists of symptom‐alleviating drugs, such as topical corticosteroids or antihistamines. Another option is potentially curative immunotherapy, currently available as sublingual and subcutaneous treatment. We investigated the potential differences in the prevalence and severity of adverse events related to subcutaneous and sublingual immunotherapy (SLIT) against grass pollen‐induced AR. A thorough literature search was performed with PubMed and EMBASE. The findings were compared with the available summaries of product characteristics (SPC) and with commercial pharmacology databases (Micromedex). The majority of available safety data originate from registered products of standardized allergens. A surprisingly large percentage of drugs, especially those used in the United States, have no systematically collected safety data. No sufficiently powered randomized trials comparing sublingual and subcutaneous immunotherapy (SCIT) were available, but general safety assessments indicate that sublingual tablet treatment is safer than subcutaneous treatment. Not all commonly used immunotherapy drugs are officially registered, and not all have systematically collected safety data. This is especially true for older drugs used in the United States. In contrast, newer drugs that have undergone extensive clinical testing have better documentation, but unified collection of safety data is still lacking. Considering the evidence available, most drugs elicit similar side effects from the same organ systems, and symptoms from the sublingual drug classes are probably less severe. However, a head‐to‐head comparison of safety and efficacy is lacking.